2005
DOI: 10.1007/11596141_5
|View full text |Cite
|
Sign up to set email alerts
|

Speaking a Common Language: A Conceptual Model for Describing Service-Oriented Systems

Abstract: Abstract. The diffusion of service-oriented computing is today heavily influencing many software development and research activities. Despite this, service-oriented computing is a relatively new field, where many aspects still suffer from a lack of standardization. Also, the service-oriented approach is bringing together researchers from different communities or from organizations having developed their own solutions. This introduces the need for letting all these people communicate with each other using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…In addition, all SQMs proposed after 2005 contain both attribute types, demonstrating an improving trend with respect to this aspect. Finally, by inspecting the evaluation of the SQM of Colombo et al [2005] according to this and the first two criteria, it can be observed that this SQM contains only atomic attributes, while its category extensiveness is flat and level of detail is fair. Such an SQM is built and structured in this way for supporting fact computation (i.e., service matchmaking and selection) algorithms which require that no interattribute dependencies exist but only QoS attributes that can be immediately measured by specific metrics without introducing higher measurement levels.…”
Section: Level Of Detail In Qualitymentioning
confidence: 99%
“…In addition, all SQMs proposed after 2005 contain both attribute types, demonstrating an improving trend with respect to this aspect. Finally, by inspecting the evaluation of the SQM of Colombo et al [2005] according to this and the first two criteria, it can be observed that this SQM contains only atomic attributes, while its category extensiveness is flat and level of detail is fair. Such an SQM is built and structured in this way for supporting fact computation (i.e., service matchmaking and selection) algorithms which require that no interattribute dependencies exist but only QoS attributes that can be immediately measured by specific metrics without introducing higher measurement levels.…”
Section: Level Of Detail In Qualitymentioning
confidence: 99%
“…The SeCSE (Service Centric System Engineering) is an EU Integrated Project of the 6 th Framework Program that aims for developing processes, methods and tools to develop service-oriented systems (Colombo et al, 2005). The SeCSE project provides a conceptual model for service oriented systems describing actors, entities and activities relevant to the service domain, and relationships between them.…”
Section: Research Issues In Model-driven Management Of Service Ecosysmentioning
confidence: 99%
“…While the conceptual model of SeCSE addresses the various steps (e.g. publication, discovery, composition and monitoring) of the service-centric system creation process, the primary purpose of the model is to provide a common understanding for human readers about the main concepts involved (Colombo et al, 2005). The primary purpose of our framework and the corresponding conceptual model is to facilitate the infrastructure services and tools needed for instrumenting service ecosystems.…”
Section: Research Issues In Model-driven Management Of Service Ecosysmentioning
confidence: 99%
“…The focus of SOSE is shifted from applications to services that are collaboratively developed by multiple SOA roles [9,10], such as service consumer, service provider, service broker. During the development process, activities like specification&modeling, design, implementation, testing, operation and maintenance are all required to be performed in a collaborative manner [11].…”
Section: The Relevance Of Cross-organizational Collaborationmentioning
confidence: 99%